Emergency medical response to hazardous materials incidents - Stilp, Richard H. (Delmar Publishers, 1997)
This text explores the medical aspects of hazardous material response including the initial response, chemical and toxicological information, effects on body systems -- injury and treatment, physiology and treatments of common poisonings. The student learns how to make decisions based on a scale of risk versus gain. Decontamination techniques, specialized equipment, simple antidotal treatments and more are discussed as they relate to the hazardous materials incident